Optical Torque Exerted on a Rotator under Illumination of a Vortex Beam - Li, Dong-Hua; Pu, Ji-Xiong; Wang, Xi-Qing (Chinese physics letters, 2012)
We investigate the torque on a specially shaped rotator produced by a vortex beam. The formulas for the torque along x, y and z directions are derived, and numerical calculation is performed. It is found that for the specially shaped rotator, the torque brought by the Laguerre-Gauss (LG) vortex beam is dependent upon the angle of the facet for each part of the rotator, and the topological charge of the vortex beam. It is shown that torque is generated from both the light momentum and orbital angular momentum (OAM) of the incident vortex beam, indicating that we can control the rotation of the rotator by modulating the OAM of the incident light beam.